Phenylalanine Effects on Brain Function in Adult Phenylketonuria. (19th January 2021) - Pilotto, Andrea; Zipser, Carl M.; Leks, Edytha; Haas, Dorothea; Gramer, Gwendolyn; Freisinger, Peter; Schaeffer, Eva; Liepelt-Scarfone, Inga; Brockmann, Kathrin; Maetzler, Walter; Schulte, Claudia; Deuschle, Christian; et al.
Abstract : Objective: To evaluate the relationship between circulating phenylalanine and brain function as well as neuropsychiatric symptoms in adults with phenylketonuria. Methods: In this prospective cross-sectional study, early-treated patients with phenylketonuria older than 30 years and age- and sex-matched controls were included. Extensive neurologic evaluation, neuropsychological and behavioral testing, sensory and motor evoked potentials, and MRI were performed. CSF concentrations of neurodegenerative markers were evaluated in addition in a subset of 10 patients. Results: Nineteen patients with phenylketonuria (median age 41 years) with different phenylalanine levels (median 873 μmol/L) entered the study. They showed higher prevalence of neurologic symptoms, cognitive and behavioral abnormalities, autonomic dysfunction, alterations in neurophysiologic measures, and atrophy in putamen and right thalamus compared to controls. In CSF, patients with phenylketonuria exhibited higher β-amyloid 1-42 ( p = 0.003), total tau ( p < 0.001), and phosphorylated tau ( p = 0.032) levels compared to controls. Plasma phenylalanine levels highly correlated with the number of failed neuropsychological tests ( r = 0.64, p = 0.003), neuropsychiatric symptoms ( r = 0.73, p < 001), motor evoked potential latency ( r = 0.48, p = 0.030), and parietal lobe atrophy. Conclusions: Our study provides strong evidence for a correlation between phenylalanine levels and clinical, neuropsychological, neurophysiologic, biochemical, and imaging alterations in adult patients with phenylketonuria.